2007
DOI: 10.1002/jobm.200710337
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of kerosene by Aspergillus ochraceus NCIM‐1146

Abstract: The filamentous fungus Aspergillus ochraceus NCIM-1146 was found to degrade kerosene, when previously grown mycelium (96 h) was incubated in the broth containing kerosene. Higher levels of NADPH-DCIP reductase, aminopyrine N-demethylase and kerosene biodegradation activities were found to be present after the growth in potato dextrose broth for 96 h, when compared with the activities at different time intervals during the growth phase. NADPH was the preferred cofactor for enzyme activity, which was inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 26 publications
2
35
0
2
Order By: Relevance
“…The major constituents of Kerosene are alkanes and cycloalkanes (65 to 70%), benzene and substituted benzene (10 to15%), naphthalene and substituted naphthalene (ASTM 2001) (Saratale et al, 2007;Wongsa et al, 2004). In this study, the greatest number of strains was isolated from the reservoir of Kerosene (13 strains); this can be related to pH that was almost neutral (pH 6.6).…”
Section: Study Of Bacterial Distribution In Various Reservoirsmentioning
confidence: 66%
See 1 more Smart Citation
“…The major constituents of Kerosene are alkanes and cycloalkanes (65 to 70%), benzene and substituted benzene (10 to15%), naphthalene and substituted naphthalene (ASTM 2001) (Saratale et al, 2007;Wongsa et al, 2004). In this study, the greatest number of strains was isolated from the reservoir of Kerosene (13 strains); this can be related to pH that was almost neutral (pH 6.6).…”
Section: Study Of Bacterial Distribution In Various Reservoirsmentioning
confidence: 66%
“…Considering that the pH is alkaline (pH 8), it was common to isolate alkalotolerant or alkalophile strains, such as SSS9 and SSS15, related to P. alcaliphila NR024734.1 and P. stutzeri CP002622.1, respectively. Saratale et al (2007) reported that Pseudomonas strains have a mixed-functional oxidase system, inducible by nalkanes as well as polyaromatic hydrocarbons. Further more, diesel oil is a complex fuel mixture, primarily consisting of paraffinic, olefinic and aromatic hydrocarbons, and smaller quantities of substances containing sulfur, nitrogen, metals, and oxygen.…”
Section: Study Of Bacterial Distribution In Various Reservoirsmentioning
confidence: 99%
“…Two or three distinct spots were observed on TLC plate after 48 h incubation by using intact mycelium (Table 4) indicates involvement of Aspergillus ochraceus in degradation of cholesterol, camphor and naphthalene by intact as well as immobilized mycelium. Aspergillus ochraceus also has ability to decolorize various industrial dyes and involvement in PAH degradation [28][29] . HPLC chromatogram of extracted sample after complete biodegradation confi rmed the degradation of camphor and cholesterol into several metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…After the addition of 0.4 ml of hexane to the incubation medium as a substrate, the reaction mixture was incubated at 37 o C for 20 min and terminated the reaction by adding 1 ml of ice cold 20% trichloroacetic acid solution. The amount of acetaldehyde liberated was estimated using Nash reagent 16,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their aggressive growth, greater biomass production and extensive hyphal growth, fungi offer potential for bioremediation technology. Fungi and other eukaryotes normally oxidize aromatic compounds using mono-oxygenase, forming a trans-diol (Saratale et al, 2007). Generally, BTHX compounds are often encountered as mixtures rather than as a single compound and the fate of these compounds is often strongly controlled by microbial activity (Mi-Seon et al, 2008).…”
mentioning
confidence: 99%